(untitled) (Boletin Médico de Postgrado, 2022)
Arterial hypertension is the most important cardiovascular risk factor in the western hemisphere. Masked hypertension (MHT), a missing link in the hypertensive syndrome for many researchers, remains an enigma to be clarified. Scientific evidence in recent years indicates that MHT is a phenomenon that is related to high rates of morbidity and mortality. The aim of this study is to describe the epidemiological profile of patients with MHT diagnosed by ambulatory blood pressure monitoring (ABPM) in the Hypertension Unit of the Centro Occidental Regional Cardiovascular Center, during the period June 2015-2020. A descriptive, cross-sectional, study was carried out which included 85 patients who met the ABPM criteria for MHT. The results show that the female sex (53%) had the highest prevalence and the mean age of the sample was 47 ± 22 years old. In 26% and 80% of patients a history of smoking and sedentary lifestyle was observed. Pathological hypersomnolence was observed in 26% of patients determined by the Epworth scale. The main associated comorbidity was diabetes (28%) followed by dyslipidemia (18%). There was a higher proportion of MHT in women, between the fifth and sixth decade of life, with a higher prevalence in patients with a history of diabetes, dyslipidemia and sedentary habits.